Performance Evaluation of Synthetic Unit Hydrograph Methods in Mediterranean Climate. A Case Study at Guvenc Micro-watershed, Turkey - Nigussie, Tewodros Assefa; Yeğen, E. Beyhan; Melesse, Assefa M. (Springer International Publishing, 2015)
Elements of hydrographs such as peak rate and time to peak are essential in the planning and design of hydraulic structures. Not two hydrographs are identical as not two watersheds and rainfall characteristics are identical. This calls for the development of hydrographs for every watershed. However, there are few number of gauged streams as the installation and management costs are expensive . Many models have been developed to overcome these problems, but these methods have not been widely used for they require lots of input parameters. As a result, a number of synthetic unit hydrograph (SUH) methods have been proposed as means of developing hydrographs for ungauged watersheds . However, their performance is not a much studied subject. This research was initiated to investigate the performance of Snyder’s, Soil Conservation Service, Mockus, Nakayasu, Rodriguez-Valdez, and Gupta-Waymire SUH methods at Guvenc micro-watershed in Turkey. Global Mapper was used to download Digital Elevation Model (DEM), and Watershed Management System (WMS) software was used to manipulate the DEM and generate necessary data in accordance with the requirements of each SUH method. The peak discharge and the time to peak were used to compare the observed unit hydrograph (UH) with the SUHs. The results of the study showed that data from internet sources could be used as a source to generate appropriate watershed characteristics necessary to derive SUH. The comparison of the elements of SUHs showed that the SCS approach performed best in simulating the peak runoff in the study area.